Manifestations of SufismIn the collection of Memory of Rhymes by the poet Nizamuddin Fadlallah (مجلة إحالات, 2026)
This research revolves around the study of the mystical phenomenon in the Diwan of Memoryof Rhymes by the Lebanese poet Nizamuddin Fadlallah, as it seeks to highlight the manifestations ofthe Sufi trend in the Diwan, especially asceticism, jihad, and the love of the Messenger and his family,may blessings and peace be upon them, and seeks to highlight the importance of Sufi studies inliterature and criticism Literary today, as literary studies today witness an increased interest in thistype of literature.